DETECTION OF PSEUDOMONAS AERUGINOSA FROM VARIOUS CLINICAL SPECIMEN AND ANTIMICROBIAL RESISTANCE PATTERN OF HUMAN - Al-Baky, Rasha Khalid Abd; Omran , Hawraa Riyadh; Abbas , Haneen Ali; Ali, Baraa Hussein; Alwan, Samer Hassan; Jalebawi, Rand Jawad (Journal of Medical Genetics and Clinical Biology, 2024)
In this study, 60 samples were collected from different sources in Al-Zahra Teaching Hospital and Karma Hospital . The random sampling process was conducted to identify the foci of pollution in P.aeruginosa, which was one of the objectives of this study and obtained diagnostic procedures. 45 samples were collected from Al-Zahra Teaching Hospital and collected from 15 samples Karma Hospital . Results of agricultural tests and tests biochemistry 10 isolates of P.aeruginosa bacteria . The pharmacological sensitivity of 10 samples was tested against 10 types of antibiotics in the method of spreading the disk to Kirby_bauer. All isolates were almost resistant . All antibiotics were resistant to severe resistance